Southern Ocean Acidification and the Antarctic Treaty System - Scott K (Edward Elgar, 2021)
This chapter explores how states party to Antarctic Treaty System instruments have addressed ocean acidification in the Southern Ocean. While there are no obligations explicitly applicable to ocean acidification, states should address the threat as part of their obligations to comprehensively protect Antarctica and its dependent and associated ecosystems, and to apply an ecosystem approach to managing Southern Ocean fisheries. The Chapter provides a critical overview of ATS initiatives to date to develop a strategic policy approach to climate change, noting the significant resistance from states to developing substantive obligations within the ATS in respect of activities taking place outside of the Antarctic Treaty area. It concludes by arguing that Article 2 of the 1991 Environmental Protocol can be interpreted to impose a due diligence obligations on parties to take action to address the causes of ocean acidification in respect of activities outside of the Antarctic Treaty area.